MEMANFAATKAN HASIL PENILAIAN KINERJA SEBAGAI PENENTU KEBIJAKAN PENGEMBANGAN KARYAWAN (Studi pada karyawan PT. BCA Tbk Cabang Borobudur Malang) - Sahertian, Pieter (Jurnal Ekonomi Modernisasi, 2005)
This research aims at the analysis of the influence of the aspect  of the performance appraisal that covers its frequency of taking the performance appraisal, the process of conducting the appraisal, the criteria of the appraisal, and also the influence of the appraisers toward the result of the appraisal itself and the influence of the result of appraisal toward the effort of developing the career of the employee.To reach the aim, an  explanatory research was designed and employed and at the same time the method of survey  was also used. The population of the research was 113 employees of PT. BCA Tbk Borobodur Branch Office Malang. The technique used was Proportional Random Sampling with the formula of Slovin, and there were 88 responden is taken as sample of the research. To measure the impact of their dependent variable toward the dependent variable F-test and t-test were used through simple and multip;e regression analysis technique.Based on the result of the regression analysis, the findings  are: (1) the frequency, the process, the criteria of the appraisal and the appraisers  simultaneously significantly influence the performance appraisal, with the contribution of 56,9%. (2) the frequency, the process, the criteria of the appraisal and the appraisers partially signicantly influence the performance appraisal, and each independent variable  mentined above gives contribution to the dependent variable 18,74%, 13,03%, 3,65%, and 17,81%. The result of the research performs a more dominant influence of the frequency of the performance appraisal toward the performance appraisal itself. (3) the variable of the result of the performance appraisal significantly influence the development of the employee’s career.